Bioaccessibility and intestinal uptake of minerals from different types of home-cooked and ready-to-eat beans - Faria, Miguel A. (2018)
Limited information exists on the bioaccessibility and intestinal uptake of essential minerals from different types of beans cooked through different cooking methods. This study aimed to estimate the in vitro bioaccessibility and intestinal uptake of the essential minerals K, Ca, Mg, Fe, Zn, Mn, Cu and Mo from four different types of beans (kidney, black, white and cowpea) cooked under different conditions (home-cooked and industrially processed canned product). Results showed that the bioaccessibility and uptake of most essential minerals is higher in canned beans. Mn was the mineral that presented the highest bioaccessibility (43–63%), and Mo had the lowest (3–36%). The highest uptake was observed for Mg (59.9%), while the lowest was found for Fe (10.5%). Regarding the type of beans, white beans presented the highest bioaccessibility and uptake for all the analyzed essential minerals and thus its consumption is preferable from a nutritional point of view.